Nonlinear system parameter identification-A modified Kalman filter algorithm - Sinha S.K.; Nagraja T. (My University, 2025)
A modified Kalman filter for parameter identification for non-linear system involves linearization, as there is no direct method available In literature. The extended Kalman filter algorithm for continuous system parameter identification given by authors [3] is applicable to nonlinear continuous system parameter identification by linearizing about the equilibrium points utilising Jacobian matrix method, Effectiveness of the desired algorithm has been illustrated by a second order example of Rayleigh's equation[6]. © 1990 IEEE.